2017
DOI: 10.1038/s41598-017-06159-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of sugammadex for reversing postoperative residual neuromuscular blockade in pediatric patients: A systematic review

Abstract: The aim of this study is to evaluate the efficacy and safety of sugammadex for reversing neuromuscular blockade in pediatric patients. MEDLINE and other three Databases were searched. Randomized clinical trials were included if they compared sugammadex with neostigmine or placebo in pediatric patients undergoing surgery involving the use of rocuronium or vecuronium. The primary outcome was the time interval from administration of reversal agents to train-of-four ratio (TOFr, T4/T1) > 0.9. Incidences of any dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
1
29
0
4
Order By: Relevance
“…Various clinical reports suggested the safety and efficacy of Sugammadex. 116 Hydroxypropyl-and sulphobutyl ether CDs are recognized as safe and used in parenteral solutions. Although these more water-soluble derivatives of CD are well-tolerated ∝-CD, β-CD and methyl-CDs are considered toxic by parenteral route.…”
Section: Safety and Efficacy Aspects Of Cyclodextrin Nanoparticlesmentioning
confidence: 99%
“…Various clinical reports suggested the safety and efficacy of Sugammadex. 116 Hydroxypropyl-and sulphobutyl ether CDs are recognized as safe and used in parenteral solutions. Although these more water-soluble derivatives of CD are well-tolerated ∝-CD, β-CD and methyl-CDs are considered toxic by parenteral route.…”
Section: Safety and Efficacy Aspects Of Cyclodextrin Nanoparticlesmentioning
confidence: 99%
“…Sugammadex is a more recent neuromuscular reversal agent that specifically targets aminosteroidal NMBDs [ 82 , 83 ]. A systematic review of randomized controlled trials reported that sugammadex produces more rapid neuromuscular reversal with less bradycardia, as compared to neostigmine and placebo [ 84 ]. The use of a nerve stimulator is important to verify the reversal of neuromuscular blockade and has been shown to be an independent factor in decreasing the risk of PRC [ 81 , 85 , 86 , 87 ].…”
Section: Preoperative Risk Assessment and Stratificationmentioning
confidence: 99%
“…A recent US study in a children's hospital also reported that children who received sugammadex were older and sicker (higher American Society of Anesthesiologists [ASA] score) than children who received neostigmine. 1 There have been systematic reviews which summarized results of randomized clinical trials on the efficacy and safety of sugammadex for reversing postoperative residual neuromuscular blockade in children, 9,10 suggesting sugammadex may be fast and effective in reversing rocuronium/ vecuronium-induced NMB in children. The FDA required postmarking randomized controlled trials among children are currently ongoing and will provide further evidence on the efficacy, safety, and pharmacokinetics of sugammadex in children.…”
Section: Discussionmentioning
confidence: 99%